PENGARUH PENCAPAIAN ISO 9001:2000 TERHADAP PENINGKATAN KUALITAS LAYANAN BELAJAR JARAK JAUH DI 11 UPBJJ-UT - Titi Chandrawati Chandrawati; Susy Puspitasari; Jasrial Jasrial (LPPM Universitas Terbuka, 2009)
Quality improvement has always been applicated by the Universitas Terbuka (UT) especially to improve its distance learning services at its regional centers. The objectives of this research are to analyze the results of the internal audit before and after the UT regional centers accepting ISO 9001:2000 certificate, to learn what the benefits of the internal audit are toward the improvement of the distance learning services in UTs regional centers, and to identify the top managers of the UTs regional centers and their staff perceptions toward the internal audit. This research was conducted between March and October 2008 in UT. The research was conducted using descriptive analysis. The report analyzing guidance, questionaires and interview guidance were employed as the research instruments. The research concluded that ISO 9001:2000 had good effects to the improvement of the distance learning services at UT regional centers. Moreover, the internal audit made the UTs regional centers did their best to improve they distance learning services and these benefits made the top managers of the UT regional centers and their staff had a good perception toward the internal audit in UT.